Novel Therapeutic Effects of Euphorbia heterophylla L. Methanol Extracts in Macular Degeneration Caused by Blue Light in A2E-Laden ARPE-19 Cells and Retina of BALB/c Mice - Ayun Seol; Ji-Eun Kim; You-Jeong Jin; Hee-Jin Song; Yu-Jeong Roh; Tae-Ryeol Kim; Eun-Seo Park; Ki-Ho Park; So-Hae Park; Muhammad Salah Uddin; Sang-Woo Lee; Young-Woo Choi; et al. (MDPI AG, 2024)
Natural products with high antioxidant activity are considered as innovative prevention strategies to effectively prevent age-related macular degeneration (AMD) in the early stage because the generation of reactive oxygen species (ROS) leading to the development of drusen is reported as an important cause of this disease. To investigate the prevention effects of the methanol extracts of Euphorbia heterophylla L. (MEE) on AMD, its effects on the antioxidant activity, inflammatory response, apoptosis pathway, neovascularization, and retinal tissue degeneration were analyzed in N-retinylidene-N-retinylethanolamine (A2E)-landed spontaneously arising retinal pigment epithelia (ARPE)-19 cells and BALB/c mice after exposure to blue light (BL). The MEE contained 10 active components and showed high free radical scavenging activity against 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), and nitric oxide (NO) radicals. The pretreatments of high-dose MEE remarkably suppressed the production of intracellular ROS (88.2%) and NO (25.2%) and enhanced (SOD) activity (84%) and the phosphorylation of nuclear factor erythroid 2-related factor 2 (Nrf2) in A2E + BL-treated ARPE-19 cells compared to Vehicle-treated group. The activation of the inducible nitric oxide synthase (iNOS)-induced cyclooxygenase-2 (COX-2) mediated pathway, inflammasome activation, and expression of inflammatory cytokines was significantly inhibited in A2E + BL-treated ARPE-19 cells after the MEE pretreatment. The activation of the apoptosis pathway and increased expression of neovascular proteins (36% for matrix metalloproteinase (MMP)-9) were inhibited in the MEE pretreated groups compared to the Vehicle-treated group. Furthermore, the thickness of the whole retina (31%), outer nuclear layer (ONL), inner nuclear layer (INL), and photoreceptor layer (PL) were significantly increased by the MEE pretreatment of BALB/c mice with BL-induced retinal degeneration. Therefore, these results suggest that the MEE, with its high antioxidative activity, protects against BL-induced retinal degeneration through the regulation of the antioxidative system, inflammatory response, apoptosis, and neovascularization in the AMD mouse model.